Optical properties of photonic crystal fibers made from Ge23Sb7S70 chalcogenide - Le, Van Hieu; Tran Hong, Tham; To Gia, Khanh; Nguyen Ba, Tu; Nguyen Thi, Thao; Nguyen Thi, Dung; Chu Van, Bien; Thi Nguyen, Hue; Nguyen Manh, An; Van Hoang, Thuy (Communications in Physics, 2025)
In this paper, we investigate a photonic crystal fiber (PCF) of Ge23Sb7S70 chalcogenide with five air-hole rings arranged in a regular hexagonal lattice. Using simulations and numerical analyses, we investigated the influence of structural parameters on the optical properties of the PCF. The results show that controlling the lattice constant (Λ) and the filling factor (f = d/Λ) in the cladding allows precise tuning of the dispersion and confinement loss properties over a wide wavelength range. Furthermore, we propose two optimized structures, #F1 (Λ = 2.0 μm, f = 0.35) and # F2 (Λ = 3.0 μm, f = 0.35), which are designed to operate in the all-normal dispersion region and the anomalous dispersion region, respectively, making them promising candidates for super-continuum generation applications.